The Caligraphy of Balinese Script as a Form of Bali Creative Industry Based on Balinese Script - Simpen, I Wayan; Udayana, I Nyoman; Rai Putra, Ida Bagus (Udayana Journal of Social Sciences and Humanities; Vol 3 No 1 (2019): UJoSSH, Feburary 2019DO - 10.24843/UJoSSH.2019.v03.i01.p03, 2019)
Based on the language mapping conducted by The Language Development and Fostering Agency, there are around 560 regional languages in Indonesia. Of all these languages, only 11 regional languages have their own literacy system. One local language that has a literacy system is Balinese. Balinese script has a vital function in the effort of documenting and transmitting various systems of knowledge found by Balinese people from the past to the present. Besides having as documentation media, Balinese script is also functional in the three important stages of Balinese people's life. From the first stage (being born), the Balinese people used the script as a provision for the burial of the placenta. During adulthood, Balinese script is also used in a tooth- cutting rite. Similarly, when the Balinese people died, Balinese script was used as rajah-rajah kajang. There are contradictions that seem to be the gap between the functionalities of Balinese script and the reality of the low knowledge of Balinese people about Balinese script. It is an indisputable fact that Latin letters dominate various spheres of life. Realizing this, it needs the effort to make people realize the potential of Balinese script in the creative process of Balinese Script Calligraphy, which is important to be studied further. Balinese script that has a rounded shape (ngawindu) is very aesthetic to be developed into aesthetic forms of a variety. Not only that, from the searches carried out in some lontar storage sites in Bali, Balinese script calligraphy contains the use of interesting language and important literary values as a medium of educational media.